Lupeol Alleviates Cerebral Ischemia–Reperfusion Injury in Correlation with Modulation of PI3K/Akt Pathway - Wang Z (Dove Medical Press, 2020)
Zhiwei Wang,1,* Yanfen Han,2,* Shujuan Tian,1 Junqiang Bao,1 Yahui Wang,3 Junping Jiao1 1Department of Internal Medicine-Neurology, The First Hospital of Hebei Medical University, Shijiazhuang City, Hebei Province 050031, People’s Republic of China; 2Department of Internal Medicine-Neurology, The Affiliated Hospital of Sergeant School of Army Medical University, Shijiazhuang City, Hebei Province 050000, People’s Republic of China; 3Department of Rehabilitation, The First Hospital of Hebei Medical University, Shijiazhuang City, Hebei Province 050031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shujuan TianDepartment of Internal Medicine-Neurology, The First Hospital of Hebei Medical University, No. 89 Donggang Road, Shijiazhuang City, Hebei Province 050031, People’s Republic of ChinaEmail prbdmhflsoxh81@163.comBackground/Aim: This study aimed to investigate the effect and mechanism of lupeol on cerebral ischemia–reperfusion injury in rats.Methods: The effects of lupeol on cerebral infarction, cerebral water content, neurological symptoms and cerebral blood flow in rats were evaluated. Nissl staining was carried out to assess the neuronal damage of ischemic brain after I/R in rats. Apoptosis of ischemic brain neurons after I/R was detected by TUNEL staining. Western blotting was carried out to detect the effects of lupeol on the expression of p-PDK1, p-Akt, pc-Raf, p-BAD, cleaved caspase-3 and p-PTEN.Results: Lupeol significantly increased cerebral blood flow after I/R in rats, reduced brain water content and infarct volume, and decreased neurological function scores. It significantly reduced neuronal damage after I/R in rats, and significantly reduced neuronal cell loss. PI3K inhibitor (LY294002) can eliminate the effect of lupeol on I/R in rats. In addition, lupeol significantly increased the protein expression of p-PDK1, p-Akt, pc-Raf, p-BAD, and down-regulated the expression of cleaved caspase-3. LY294002 reversed the effects of lupeol on the expression of PI3K/Akt signaling pathway-related proteins and cleaved caspase-3 after I/R in rats.Conclusion: Lupeol had significant neuroprotective effects on brain I/R injury and neuronal apoptosis, and its mechanism may be related to the activation of PI3K/Akt signaling pathway.Keywords: lupeol, PI3K/Akt, apoptosis, cerebral ischemia/reperfusion (I/R) injury